2008
DOI: 10.1002/hep.22403
|View full text |Cite
|
Sign up to set email alerts
|

Albinterferon alfa‐2b dosed every two or four weeks in interferon‐naïve patients with genotype 1 chronic hepatitis C†‡

Abstract: The efficacy and safety of albinterferon alfa-2b (alb-IFN), a novel recombinant protein consisting of interferon alfa-2b genetically fused to human albumin, was evaluated in a phase 2b, open-label study of patients with genotype 1, chronic hepatitis C. In all, 458 IFN-alfa treatment-naïve patients were randomized to 48-week treatment with peginterferon alfa (PEG-IFN␣)-2a 180 g one time per week (qwk), or alb-IFN 900 or 1,200 g once every two weeks (q2wk), or 1,200 g once every four weeks (q4wk), administered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 17 publications
2
49
0
2
Order By: Relevance
“…In vivo studies in cynomolgus monkeys revealed a prolonged halflife of alb-IFN in comparison with IFN-a (Osborn et al, 2002). The efficacy of alb-IFN was evaluated in clinical phase IIb studies with IFN-naive patients chronically infected with HCV, in which it was administered every 2 or 4 weeks (Zeuzem et al, 2008). The clinical studies showed that alb-IFN had similar anti-viral effects to pegIFN-a (Nelson et al, 2010;Zeuzem et al, 2010).…”
Section: New Ifnsmentioning
confidence: 99%
“…In vivo studies in cynomolgus monkeys revealed a prolonged halflife of alb-IFN in comparison with IFN-a (Osborn et al, 2002). The efficacy of alb-IFN was evaluated in clinical phase IIb studies with IFN-naive patients chronically infected with HCV, in which it was administered every 2 or 4 weeks (Zeuzem et al, 2008). The clinical studies showed that alb-IFN had similar anti-viral effects to pegIFN-a (Nelson et al, 2010;Zeuzem et al, 2010).…”
Section: New Ifnsmentioning
confidence: 99%
“…5.3.6 New therapies for hepatitis C Several new therapeutic avenues are being explored for the treatment of hepatitis C. These include new forms of interferon, ribavirin analogues, and direct antiviral agents including protease inhibitors and polymerase inhibitors [222][223][224][225][226][227]. None of these new agents has been subject to clinical trial yet in HIV-positive patients.…”
Section: Nonresponders and Relapsersmentioning
confidence: 99%
“…55,5% und für die 4-wöchige Applikation 50,9%. Im Kontrollarm (Peginterferon alfa-2a) zeigten 57,9% der Patienten eine anhaltende virologische Therapieantwort [26]. In der in Kürze abgeschlossenen Zulassungsstudie wurde auf den 4-wö-chigen Albumin-Interferon-Arm verzichtet.…”
Section: Albumin-interferonunclassified